First report of hare treponematosis seroprevalence of European brown hares (Lepus europaeus) in the Czech Republic: seroprevalence negatively correlates with altitude of sampling areas - Nováková, Markéta; Najt, David; Mikalová, Lenka; Kostková, Marcela; Vrbová, Eliška; Strouhal, Michal; Posautz, Annika; Knauf, Sascha; Šmajs, David (BMC veterinary research, 2019)
BACKGROUND: The aim of this study was to quantify the seroprevalence of hare treponematosis in European brown hare (Lepus europaeus) populations in the Czech Republic and to test for an association between treponematosis prevalence and the altitude of the areas in which hares were sampled. We tested 289 serum samples of brown hares collected between 2015 and 2017. The sampling areas included 12 districts (73 villages) distributed throughout the Czech Republic. Serum samples were tested for the presence of antibodies against the causative agent of hare treponematosis (Treponema paraluisleporidarum ecovar Lepus, TPeL) using two serological tests for human syphilis that cross-react with TPeL: the Treponema pallidum hemagglutination assay (TPHA) and the fluorescent treponemal antibody absorption (FTA-ABS) test. To account for the imperfect diagnostic sensitivity and specificity of each test, apparent prevalence estimates of TPeL were converted to true prevalence estimates using the Rogan Gladen estimator. The correlation between TPeL true seroprevalence and altitude of sampling areas was analyzed using Pearson's correlation coefficient at three levels of spatial resolution: (1) four groups, each composed of two merged districts, with ≥20 samples collected, differing in their altitude median (206, 348, 495, and 522 m above sea level); (2) separately tested eight districts, where ≥20 samples were collected per district; and (3) 27 groups composed of villages of the same altitude level distributed across the whole dataset. RESULTS: One hundred and seven of the 289 samples were seropositive to both tests, the FTA-ABS test was positive for an additional 47 samples. Seropositive samples were found in all 12 districts. True seroprevalence of TPeL in the sampled hares was 52% (95% confidence interval 46 to 58%). A statistically significant negative correlation between TPeL seroprevalence and altitude was identified at the district level (Pearson's r = - 0.722, p = 0.043). CONCLUSIONS: Between 2015 and 2017 hare treponematosis was present at a relatively high prevalence in brown hares in all 12 districts in the Czech Republic where sampling was carried out. The seroprevalence of TPeL in brown hares was negatively correlated with the altitude of the areas in which hares were sampled.
Keywords: séroepidemiologické studie; Treponemal Infections; Animals; mužské pohlaví; Hares; ženské pohlaví; nadmořská výška; zvířata; Female; Altitude; Seroepidemiologic Studies; Czech Republic; infekce bakteriemi rodu Treponema; Male; zajíci; Česká republika